Pengembangan Usaha Ekonomi Perdagangan Berbasis Kearifan Lokal Pada Kelompok Usaha Masyarakat Desa Hambaro - Fina Ananda Putri; Anisa Nurmaida; Muhammad Adam Kusuma; Muhammad Sahrul (UNIB Press, 2023)
Hambaro Village is a village that is rich in natural potential both from the agricultural, plantation, livestock and fisheries sectors. Hambaro Village is located in the Nanggung sub-district, Bogor Regency, West Java. In this Community Service Activity, we chose the hambaro village in order to increase information, knowledge and skills related to product packaging so that it can improve the village economy in the community, especially in Kampung Pabuaran Tengah. This community service also aims to establish collaboration between communities, business groups, and government in developing economic businesses while maintaining existing local wisdom, increasing business management education both to existing business groups and startup groups, forming awareness of the potential both in aspects of human resources and natural resources, the creation of business groups that do not only focus on profit alone but are also based on sociopreneurs.